(1 + 2y) / (y-4) = (4y ^ 2 + 5y) / (2y ^ 2-7y-4) nasıl çözülür?

(1 + 2y) / (y-4) = (4y ^ 2 + 5y) / (2y ^ 2-7y-4) nasıl çözülür?
Anonim

# (1 + 2y) / (y-4) = (R4y ^ 2 + 5y) / (2y ^ 2-7y-4) #

  • çarpanlara ayırmak sağ taraf:

# (4y ^ 2 + 5y) / renk (kırmızı) (2y ^ 2-8y + y-4) #

# (4y ^ 2 + 5y) / renkli (kırmızı) (2y, (y-4) + 1, (y-4) #

# = (4y ^ 2 + 5y) / (1 + 2y), (y-4) #

  • İlk denklemi kullanarak:

# (1 + 2y) / renk (kırmızı) iptal da (y-4) = (R4y ^ 2 + 5y) / (1 + 2y) renkli (kırmızı) iptal ((y-4) #

  • Çapraz Çarp

#color (kırmızı) (+ 2y 1) ^ 2 = 4y ^ 2 + 5y #

Genişlemeye göre: # -> (a + b) ^ 2 = a ^ 2 + 2ab + B ^ 2 #

#color (kırmızı) 1 + 4y + iptal (R4y ^ 2) = iptal (R4y ^ 2) + 5y #

CEVAP

• y = 1 #

Bir göz atın: